Deconstructing the Domestic Role of the Wife in Community Tradition: An Analysis of Maqāṣid al-Sharī‘ah and Marriage Law - Moh. Irham Maulana; Dzulfikar Rodafi; Nur Hasan (Bulletin of Indonesian Islamic Studies, 2025)
Domestic role inequality remains an issue in rural Indonesian society, including in Separah Village, Bangkalan. The burden of household chores is entirely borne by the wife, even when they are also involved in economic activities, leading to a dual burden that has implications for gender equality and family well-being. This study aims to examine this practice by placing it within the framework of maqāṣid al-sharī‘ah and the Marriage Law. The method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, participant observation, and documentation from married couples, community leaders, and religious figures. The analysis was conducted descriptively and critically, linking field data with the principles of gender justice. The research findings indicate that the dominance of local traditions and low legal literacy make the division of domestic labor inconsistent with both Islamic law and state law. The role of religious figures in providing education is also still passive. Nevertheless, there are signs of change among young people who are starting to build more equal family relationships thanks to education, digital access, and progressive religious discourse. This research confirms that the domestic role is a social construct that needs to be reinterpreted within the framework of maqāṣid al-sharī‘ah, while also serving as the basis for strengthening legal literacy and cultural intervention toward just and collaborative household relationships.